2019
DOI: 10.3390/w11091805
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Crop Production in Uganda—An Integrated Systems Assessment with Water and Energy Implications

Abstract: With less than 3% of agricultural cropland under irrigation, subsistence farmers in Uganda are dependent on seasonal precipitation for crop production. The majority of crops grown in the country-especially staple food crops like Matooke (Plantains)-are sensitive to the availability of water throughout their growing period and hence vulnerable to climatic impacts. In response to these challenges, the Government has developed an ambitious irrigation master plan. However, the energy implications of implementing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Finally, rainfall was associated with maize, rice, or cassava yields in any state. Many other studies have reported the similar finding of the climate-crops relationships in China (Zhang et al 2016;Gao et al 2019;Ding et al 2020), Southern Africa (Mafongoya et al 2017;Nhamo et al 2019) and East African countries (Sridharan et al 2019;Thomas et al 2019). These results dovetail with results from previous research.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, rainfall was associated with maize, rice, or cassava yields in any state. Many other studies have reported the similar finding of the climate-crops relationships in China (Zhang et al 2016;Gao et al 2019;Ding et al 2020), Southern Africa (Mafongoya et al 2017;Nhamo et al 2019) and East African countries (Sridharan et al 2019;Thomas et al 2019). These results dovetail with results from previous research.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, rainfall was associated with maize, rice, or cassava yields in any state. Many other studies have reported the similar finding of the climate-crops relationships in China (Zhang et al 2016;Gao et al 2019;Ding et al 2020), Southern Africa (Mafongoya et al 2017;Nhamo et al 2019) and East African countries (Sridharan et al 2019;Thomas et al 2019). These results dovetail with results from previous research.…”
Section: Resultssupporting
confidence: 55%
“…For Uganda, several climate change studies (e.g., [16][17][18]) projected precipitation increase. However, the investigation of the concomitant future changes in both precipitation and evapotranspiration across Uganda is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous climate change studies in Uganda were either limited to a catchment scale or did not consider differences in the hydro-climates of the various sub-regions [16][17][18][26][27][28]. This shows that there is limited information for adaptive planning of water resources management across the various WMZs in Uganda.…”
Section: Introductionmentioning
confidence: 99%